An educational awareness program to reduce energy consumption in schools. (1st January 2021) - Pietrapertosa, Filomena; Tancredi, Marco; Salvia, Monica; Proto, Monica; Pepe, Angelo; Giordano, Michele; Afflitto, Nicola; Sarricchio, Giuliano; Di Leo, Senatro; Cosmi, Carmelina
Abstract: Energy consumption can be significantly reduced by targeting consumers behaviour to achieve sustained energy savings and promote sustainable consumption patterns. In this context, the younger generations are a privileged target group to promote virtuous energy behaviours in the whole community. This paper describes the Schools4energy initiative, a program developed within the Interreg MED PrioritEE project, aimed at increasing energy efficiency in municipal public buildings by raising energy awareness in public schools while demonstrating the effectiveness of pupils' engagement to promote energy savings through virtuous behaviours. Schools4energy was based on a multifold "learning by doing" methodology implemented in the Living Lab of the Potenza case study. During the 2018/2019 school year, children aged between 3 and 14 belonging to four primary and middle schools owned by the Municipality of Potenza (Southern Italy) were involved in three sets of activities designed to valorise the power of young generation in promoting more conscious behaviours: a competition among schools to reduce energy consumption (School Race) based on the adoption of good energy practices based on a common Energy Charter, an artistic competition among students to support creative thinking (Art4energy) and gamification as an alternative method to learn about energy (Play4energy). The consumptions of natural gas and electricity were monitored from August 2018 to April 2019 to highlight the effects of the adoption of Energy Charter in terms of energy and money saved. Data analysis highlighted different trends among the participating schools, underlining their different commitment and the infrastructural barriers. Despite the harsher winter, an average decrease of 4% in natural gas consumption was observed in the school in which energy saving measures complemented technical interventions and a limited increase in electricity consumption (between 0.5% and 4.3% per capita), which led to savings on the energy bill of about 1122 Euro. The enthusiastic participation of the children highlighted the great potential of educational programmes in driving a steady change of mentality in the society. Graphical abstract: Image 1 Highlights: A Living Lab was developed to boost energy saving in public schools. A "learning by doing" method to raise energy awareness was implemented. School competition encourages all schools' occupants to save energy. Virtuous energy behaviours are learned at school and brought back to homes. The best result is a 4% reduction of gas and a slight increase in electricity (0.5%).